2013
DOI: 10.1111/mms.12008
|View full text |Cite
|
Sign up to set email alerts
|

Decline in local abundance of bottlenose dolphins (Tursiops truncatus) in the Bay of Islands, New Zealand

Abstract: Regional populations of bottlenose dolphins (Tursiops truncatus) around New Zealand are genetically isolated from each other and the species was recently classified as nationally endangered based on relatively small population sizes and reports of high calf mortality. Here, we estimate the abundance and trends in one of these regional populations, the Bay of Islands, using a photo‐identification database collected from 1997 to 1999 and from 2003 to 2006, containing a total of 3,841 records of 317 individual do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
46
2
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(52 citation statements)
references
References 39 publications
3
46
2
1
Order By: Relevance
“…Similarly, some dolphins may only visit the area rarely (i.e. transient dolphins), something that has also has been noted for BOI (Tezanos-Pinto et al 2013).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Similarly, some dolphins may only visit the area rarely (i.e. transient dolphins), something that has also has been noted for BOI (Tezanos-Pinto et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Mann et al (2000) found bottlenose dolphin group sizes were largest for groups with calves up to 3 mo old, which may also in part explain the formation of large groups at GBI given the high frequency of neonates and calves recorded. Based on the variable patterns of site fidelity and habitat use observed in BOI (Constantine 2002, Tezanos-Pinto 2009, Hartel et al 2014, Tezanos-Pinto et al 2013, we anticipated new individuals would continue to be photo-identified for the duration of the study. The discovery curve reached a plateau after 17 mo of field effort, although a further 8 new individuals were added to the catalogue in the final summer season.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations